One-Pot Route from Halogenated Amides to Piperidines and Pyrrolidines - Qiao Song; Sheng Wang; Xiangui Lei; Yan Liu; Xin Wen; Zhouyu Wang (Molecules, 2022)
Piperidine and pyrrolidine derivatives are important nitrogen heterocyclic structures with a wide range of biological activities. However, reported methods for their construction often face problems of requiring the use of expensive metal catalysts, highly toxic reaction reagents or hazardous reaction conditions. Herein, an efficient route from halogenated amides to piperidines and pyrrolidines was disclosed. In this method, amide activation, reduction of nitrile ions, and intramolecular nucleophilic substitution were integrated in a one-pot reaction. The reaction conditions were mild and no metal catalysts were used. The synthesis of a variety of N-substituted and some C-substituted piperidines and pyrrolidines became convenient, and good yields were obtained.